WIMAX LINK PERFORMANCE ANALYSIS FOR WIRELESS AUTOMATION APPLICATIONS - Ailen-Ubhi, Samuel Olusegun (My University, 2012)
Wireless broadband access technologies are rapidly growing and a corresponding growth in the demand of its applicability transcends faster internet access, high speed file download and different multimedia applications such as voice calls, video streaming, teleconferencing etc, to industrial operations and automation. Industrial and automation systems perform operations that requires the transmission of real time information from one end to another through high-performance wireless broadband communication links. WiMAX, based on IEEE 802.16 standard is one of the wireless broadband access technologies that has overcome location, speed, and access limitations of the traditional Digital Subscriber Line and Wireless Fidelity, and offers high efficient data rates. This thesis presents detailed analysis of operational WiMAX link performance parameters such as throughput, latency, jitter, and packet loss for suitable applicability in wireless automation applications. The theoretical background of components and functionalities of WiMAX physical and MAC layers as well as the network performance features are presented. The equipment deployed for this field experiment are Alvarion BreeZeMAX 3000 fixed WiMAX equipment operating in the 3.5 GHz licensed band with channel bandwidth of 3.5 MHz. The deployed equipment consisting of MBSE and CPE are installed and commissioned prior to field tests. Several measurements are made in three link quality scenarios (sufficient, good and excellent) in the University of Vaasa campus. Observations and results obtained are discussed and analyzed.
Keywords: WiMAX; Physical Layer; MAC Layer; Performance; Analysis; Automation; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|